Fires and human activities as key factors in the high diversity of Corsican vegetation. (February 2020) - Lestienne, Marion; Jouffroy-Bapicot, Isabelle; Leyssenne, Déborah; Sabatier, Pierre; Debret, Maxime; Albertini, Pierre-Jean; Colombaroli, Daniele; Didier, Julien; Hély, Christelle; Vannière, Boris
In the Mediterranean region, Corsica represents one of the most important hotspots of biodiversity, partly due to the high number of endemics species. This region is also one of the most affected by forest fires worldwide. The present vegetation is adapted to a wide range of disturbance regimes, but a change in fire frequency or intensity in the future may severely affect ecological resources and other socio-economical aspects. Here, we study the dynamics of vegetation–human–fire interactions for the past 12, 000 years as recorded by Lake Bastani (Corsica, France). We used well-dated sedimentary records of charcoal, pollen and fungal spores to infer past fire regime, land cover and pastoral activities, respectively, and we compared our results with charcoal records from two other Corsican lakes (Nino and Creno, respectively). Our results suggest that climate and natural fires were the main factors shaping the landscape before 5000 cal. BP. Then, the extraordinary diversity of the current Corsican vegetation has been mainly promoted by human activities on the island (i.e. deforestation and pastoralism) at least from the Bronze Age (3500 cal. BP). The top of our record shows a sharp decrease in fungal remains ( Sporormiella -type), usually associated with pastoral activities, which could be attributed to the land abandonment occurring since a few decades.